10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
PurposeHealth communication campaigns are an effective and widely used approach to changing health-related behaviours and thus represent a potential means by which vaping among young people can be addressed. To inform the development of future campaigns, this study aimed to document the communication approaches being used in vaping prevention advertisements internationally and understand the extent to which evidence-based principles are being adopted in practice.DesignHealth campaign video advertisements discouraging vaping were sourced online. Eligible ads were produced in English, released between January 2013 and December 2024, and no longer than 60 seconds in length.SettingOnline.SampleA total of 199 unique ads from 5 countries met inclusion criteria.AnalysisAds were coded according to a pre-defined framework of advertising approaches.ResultsThe majority of ads used high certainty language (89%) and were negatively valenced (88%). Most adopted a cognitive approach (70%) and were assessed as having a dogmatic language style (64%). Two-thirds (66%) communicated messages relating to the chemical ingredients present in vapes. In terms of execution styles, inducing fear was most common (74% of ads).ConclusionWhile some of the approaches being adopted in real-world vaping prevention ads have demonstrated efficacy in the context of simulated experiments (e.g., high linguistic certainty), other approaches do not (e.g., dogmatic language). Additional research exploring the outcomes of specific approaches is needed to guide the development of optimally effective vaping prevention communications.